Vitamin D status of children with lower respiratory tract infections and its correlation with severity of pneumonia: A comparative study - Mohammed Mujtaba Qureshi,; Saifuddin, Mohammed (Asian Journal of Medical Sciences, 2022)
Background: Acute lower respiratory tract infections (LRTI) is responsible for considerable morbidity and mortality among pediatric age group and remains one of the common causes for pediatric intensive care unit admissions. Vitamin D deficiency is one of the important risk factors not only for the occurrence but also for the increased severity of LRTI. We undertook this study to analyze vitamin D status of children admitted for LRTI and to find out its correlation with severity of LRTI. Aims and Objectives: The aims of this study were as follows: (1) To find out vitamin D status of children presenting with LRTI and (2) to find out correlation of vitamin D levels with severity of LRTI. Materials and Methods: This was a hospital-based comparative study, in which 60 children below age of 5 years and admitted for acute LRTI were included on the basis of a predefined inclusion and exclusion criteria (Group A). Sixty other children admitted for non-respiratory causes were included as control group (Group B). Vitamin D status of children in both the groups was determined. The severity of LRTI and its correlation with vitamin D status was determined. P<0.05 was taken as statistically significant. Results: There was a male predominance in both the groups. The mean age of patients in Group A and Group B was found to be 17.70±7.80 months and 18.41±7.11 months, respectively (P>0.005). In Group A, 42 (70%) patients were having bronchiolitis, whereas bronchopneumonia was seen in 16 (26.67%) patients and two patients (3.33%) were found to have lobar pneumonia. Forty-eight (80%) children were having pneumonia and remaining 12 (20%) children were found to have severe pneumonia. Higher number of children were either vitamin D inefficient or deficient in Group A as compared to Group B and the difference was found to be statistically highly significant (P<0.0001). The mean 25 (OH) D levels were found to be low in patients with severe pneumonia as compared to pneumonia and the difference was found to be statistically highly significant (P<0.0001). Conclusion: Lower levels of vitamin D were found to be a risk factor not only for the development but also for severity of LRTI. Determination and management of vitamin D deficiency status is one of the important parts of management of children with LRTI.